Indigenous knowledge of the people in Karya Usaha Hamlet (Kubu Raya, West Kalimantan, Indonesia) on the processing and diversity of plants that enhance toddler's appetite - RUQIAH GANDA PUTRI PANJAITAN; MITALIA MITALIA; Ruhyat Partasasmita (Society for Indonesian Biodiversity, 2020)
Abstract. Panjaitan RGP, Mitalia, Partasasmita R. 2020. Indigenous knowledge of the people in Karya Usaha Hamlet (Kubu Raya, West Kalimantan, Indonesia) on the processing and diversity of plants that enhance toddler's appetite. Biodiversitas 21: 4284-4290. Traditional medicines derived from plants are widely consumed daily by the people of Karya Usaha Hamlet in Indonesia. Not only it is used by adults but also children under the age of five, to increase their appetites. This information was the key to a scientific assessment as it was an effort for health resilience in the community. Therefore, this study aimed to understand the diversity of plant species that is prospective to enhance the toddler's appetite and its process. The method used in this study was a qualitative analysis using a semi-structured interview technique with several informants, which consisted of midwives, health service workers, Posyandu cadres, and people from the ethnic origin. The parts of the plants used as traditional medicinal ingredients were subjected to a qualitative phytochemical screening. The results revealed that seven species were potential as appetite enhancers for toddlers. Furthermore, sixty percent of the informants exhibited Javanese turmeric (Curcuma xanthorrhiza Roxb.) mainly as herbal medicine, while 25.8% and 14.2% chose the fingerroot (Boesenbergia pandurata (Roxb.) Schlecht.) and common turmeric (Curcuma domestica L.), respectively, as main herbal medicine. On the other hand, flavor enhancers on food from the diversity of plants used mostly by midwives in the village were on average of 2.19 species. Medicinal plants were generally processed by boiling and further adding honey or sugar so that children under the age of five will have a sweet flavor as they drink it.